Estructura financiera de los ingresos públicos en la Municipalidad Distrital de San Juan Bautista, periodo 2019 – 2023 - Tello Chota, Oswaldo Nilo (2025)
Knowing the financial structure of public income in an entity or institution is very important in its management, since it helps to understand and understand its composition and characteristics, in such a way, it allows making correct decisions in order to increase the collection of the public income. public resources. The research focuses on knowing the financial structure of public income in the District Municipality of San Juan Bautista, the study has a scope of five (05) years ranging from 2019 to 2023, the population is made up of all records linked only to public revenues, procedures were developed where techniques such as selective review, analysis and calculation were used, the instrument was the data collection sheet, all of which facilitated the extraction of information; Regarding the methodology used, it had a quantitative approach, with a descriptive level and non-experimental – longitudinal design. Finally, the results reveal that the financial structure is composed of common funds, municipal taxes, directly collected resources, donations and transfers, canon and overcanon, royalties and resources from official operations.